Uncertainty in Historical Land-Use Reconstructions with Topographic Maps - Kaim, Dominik; Kozak, Jacek; Ostafin, Krzysztof; Dobosz, Monika; Ostapowicz, Katarzyna; Kolecka, Natalia; Gimmi, Urs (Quaestiones Geographicae, 2014)
The paper presents the outcomes of the uncertainty investigation of a long-term forest cover change analysis in the Polish Carpathians (nearly 20,000 km2) and Swiss Alps (nearly 10,000 km2) based on topographic maps. Following Leyk et al. (2005) all possible uncertainties are grouped into three domains - production-oriented, transformation- oriented and application-oriented. We show typical examples for each uncertainty domain, encountered during the forest cover change analysis and discuss consequences for change detection. Finally, a proposal for reliability assessment is presented.